2017
DOI: 10.1002/cav.1771
|View full text |Cite
|
Sign up to set email alerts
|

The effects of virtual human's spatial and behavioral coherence with physical objects on social presence in AR

Abstract: In augmented reality, people can feel the illusion of virtual humans (VHs) integrated into a real (physical) space. However, affordances of the real world and virtual contents might conflict, for example, when the VHs and real objects "collide" by occupying the same space. This implausible conflict can cause a break in presence in real-virtual human interactions. In this paper, we address an effort to avoid this conflict by maintaining the VH's spatial and behavioral coherence with respect to the physical obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(27 citation statements)
references
References 13 publications
0
27
0
Order By: Relevance
“…the help from Internet of Things (IoTs) actuators, VOs now can affect physical space. Such physical-virtual interactions are known to have positive effects on users' perception of the VOs [16,19,20].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…the help from Internet of Things (IoTs) actuators, VOs now can affect physical space. Such physical-virtual interactions are known to have positive effects on users' perception of the VOs [16,19,20].…”
mentioning
confidence: 99%
“…Not only that, but they also likely lead to incorrect mutual occlusion between ROs and VOs, causing depth distortion [18]. Moreover, ROs intruding the place occupied by VOs could lead to an issue known as physicality conflicts [16,24]. Some of these problems related to mutual occlusion can be resolved by applying advanced technologies [14,28].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…If the two spaces are different, this simple strategy may cause unnaturalness in the avatar's motion (e.g., environment penetration, sitting in the air, etc. ), which can degrade the immersiveness [Kim et al 2017]. Therefore, the avatar's placement and movement need to be modified to fit the target space in AR telepresence.…”
Section: Related Workmentioning
confidence: 99%
“…Using these mediums provides new opportunities for human-agent interaction. For instance, Kim et al have shown that agent awareness of the physical and virtual environment in AR can have positive impacts on social presence and user behavior [52,54,55]. AR is anticipated to eventually become an even larger market than VR [3], and it can be an effective platform for IVAs.…”
Section: Emerging Trends and Directionsmentioning
confidence: 99%